Reading books and watching films as a protective factor against suicidal ideation - Kasahara-Kiritani, Mami; Brunner, Romuald; Kaess, Michael (International journal of environmental research and public health, 2015)
Reading books and watching films were investigated as protective factors for serious suicidal ideation (SSI) in young people with low perceived social belonging. Cross-sectional and longitudinal (12-month) analyses were performed using data from a representative European sample of 3256 students from the “Saving and Empowering Young Lives in Europe” study. Low social belonging was associated to SSI. However, reading books and watching films moderated this association, especially for those with lowest levels of belonging. This was true both at baseline and at 12 months of follow-up analyses. These media may act as sources of social support or mental health literacy and thus reduce the suicide risk constituted by low sense of belonging.